Multinational evaluation of the BioFire® FilmArray® Pneumonia plus Panel as compared to standard of care testing - Christine C. Ginocchio; Carolina Garcia-Mondragon; Barbara Mauerhofer; Cory Rindlisbacher; L. Forcelledo; J. Fernández; R. Lienhard; H. Kerschner; G. M. Rossolini; L. Armand-Lefèvre; C. d’Humières; E. Cambau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
This study compared standard of care testing (SOC) to BioFire® FilmArray® Pneumonia plus Panel (PN plus ). PN plus detects 15 bacteria with semiquantitative log bin values, 7 antibiotic resistance markers, three atypical bacteria (AB), and eight viral classes directly from bronchoalveolar lavage-like specimens (BLS) and sputum-like specimens (SLS). Fifty-two laboratories from 13 European countries and Israel tested 1234 BLS and 1242 SLS with PN plus and SOC. Detection rates and number of pathogens/samples were compared for PN plus pathogens. PN plus bin values and SOC quantities were compared. Three thousand two hundred sixty-two bacteria in PN plus were detected by PN plus and/or SOC. SOC detected 57.1% compared to 95.8% for PN plus ( p ≤ 0.0001). PN plus semiquantitative bin values were less than SOC, equal to SOC, or greater than SOC in 5.1%, 25.4%, and 69.6% of results, respectively. PN plus bin values were on average ≥ 1 log than SOC values (58.5% 1–2 logs; 11.0% 3–4 logs). PN plus identified 98.2% of MRSA and SOC 55.6%. SOC detected 73/103 AB (70.9%) and 134/631 viruses (21.2%). PN plus detected 93/103 AB (90.3%) and 618/631 viruses (97.9%) ( p ≤ 0.0001). PN plus and SOC mean number of pathogens/samples were 1.99 and 1.44, respectively. All gram-negative resistance markers were detected. PN plus and SOC results were fully or partially concordant for 49.1% and 26.4% of specimens, respectively. PN plus was highly sensitive and detected more potential pneumonia pathogens than SOC. Semiquantification may assist in understanding pathogen significance. As PN plus generates results in approximately 1 h, PN plus has potential to direct antimicrobial therapy in near real time and improve antimicrobial stewardship and patient outcomes.

Influence of oceanic factors on long-distance movements of loggerhead sea turtles displaced in the southwest Indian Ocean - Resi Mencacci; Elisabetta De Bernardi; Alessandro Sale; Johann R. E. Lutjeharms; Paolo Luschi (Marine Biology, 2010)

Satellite tracking of migrating loggerhead sea turtles (Caretta caretta) displaced in the open sea - P. Luschi; G. R. Hughes; R. Mencacci; E. De Bernardi; A. Sale; R. Broker; M. Bouwer; F. Papi (Marine Biology, 2003)